PALANG PINTU: POLITIK IDENTITAS LAKI-LAKI MINANGKABAU SEBAGAI SEBUAH RESPON TERHADAP STIGMA JANDA - Jelly, Jelly; Afrizal, Afrizal; Delfi, Maskota (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
This article discusses Minangkabau male identity politics in response to the widow's stigma. The method of collecting data are interview and observation. Minangkabau is a society that adopt a matrilineal system. The lineage, management and utilization of inheritance are in the hands of women. The present of men like abu di ateh tunggua (second lead and weak). This condition maked the man use identity political and maked stigma for widows in their social life. Man strengthen their position as palang pintu for widows. Man used maota dan malapau as tools to grow up their position. (This study uses the concept of stigma by Parker (2016).